2017
DOI: 10.1002/tl.20239
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges from the Decoding Interview to Teaching Practice

Abstract: This chapter describes a multidisciplinary faculty self-study about reciprocity in service-learning.The study began with each co-author participating in a Decoding interview. We describe how Decoding combined with collaborative self-study had a positive impact on our teaching practice. The experience of this group of students and their professors, two co-authors of this chapter, is all too common and not an isolated incident. This is not surprising given that it has been argued that "service learning pedagogy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Our analysis did not account for differences among the four service-learning programs. Given the growing field of international service-learning scholarship, including studies of intervention strategies (Sturgill & Motley, 2014), intercultural competence development (Deardorff & Edwards, 2015), and building reciprocity with local partners in service learning (Pettit et al, 2017;Tiessen, Lough, & Cheung, 2018), we believe we have much to learn by further exploration into our programs' structures of interaction and activities. Finally, our findings related to effects of intra-group dynamics were unexpected, in that they only emerged in our final round of qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis did not account for differences among the four service-learning programs. Given the growing field of international service-learning scholarship, including studies of intervention strategies (Sturgill & Motley, 2014), intercultural competence development (Deardorff & Edwards, 2015), and building reciprocity with local partners in service learning (Pettit et al, 2017;Tiessen, Lough, & Cheung, 2018), we believe we have much to learn by further exploration into our programs' structures of interaction and activities. Finally, our findings related to effects of intra-group dynamics were unexpected, in that they only emerged in our final round of qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Miller-Young's (2015) self-study found that group dialogue during interviews generated deeper understandings of the disciplinary concept of reciprocity and states that expert thinking is "inclined towards an epistemology in which knowledge construction is never finished or complete" (Miller-Young 2015, 40). Similarly, Pettit (2017), Lee-Post (2019), Pace (2011), Schlegel (2004) and Grim et al (2004) found that active participation amongst students generates new forms of questioning that appear to be powerful tools for reflection. Without precluding the importance of autonomous learning, such team effort facilitates disciplinary skill development (Schlegel 2004) and allows tasks to be skilfully analysed, dissected (Grim et al 2004) and deconstructed.…”
Section: Making Expert Habits Of Mind More Explicit For the Novice Le...mentioning
confidence: 97%
“…The remaining 8 studies (Attas 2018;Diaz 2008;Fischer 2018;Sturts and Mowatt 2012;Miller 2018;Miller-Young 2015;Middendorf and Pace 2004;Pettit 2017) identified tacit mental operations that are often mistakenly assumed in student learning: The disciplinary practitioner knows that prescribed scholarly material do not represent the only opinion on a matter (Attas 2018;Schlegel 2004;Pace 2004;Pettit 2017) and that learners should seek other conflicting perspectives. By voicing their own interpretations (Diaz 2008), learners would soon realise that they are not passive consumers of knowledge but that they are able to become active contributors to scholarship.…”
Section: Perceiving Scholarship As Dialogicmentioning
confidence: 99%
See 2 more Smart Citations